The Impact of Company Growth and Company Size on Dividend Policy in Automotive and Component Sub-Sector Companies Listed on the Indonesian Stock Exchange During the Period 2020–2023 - Bintang, Fachwadi; Mursalini, Wahyu Indah; Yeni, Afni (CV. Proaksara Global Transeduka, 2025)
This research seeks to examine and evaluate how corporate growth and firm size influence dividend policy among manufacturing companies in the automotive and components subsector from 2020 to 2023. The study employs a quantitative methodology and focuses on 18 manufacturing firms in the automotive and components subsector that are publicly traded on the Indonesia Stock Exchange during the specified timeframe. Through purposive sampling methods, the researchers selected 15 companies from this subsector for analysis. The analytical approach utilized multiple linear regression analysis conducted with SPSS version 19 software. The findings reveal that corporate growth does not significantly impact dividend policy decisions, whereas firm size demonstrates a positive and statistically significant influence on dividend policy. When examining the combined effect of both variables, the results indicate that company growth and firm size together influence dividend policy, though this collective impact lacks statistical significance.